Origin of pyrite nodules at the top of the nantuo diamictites, Southern China - Changjie Liu (Nature Portfolio, 2021)
Abstract Pyrite nodules up to 20 cm in diameter are found at the top of the Marinoan (~ 635 Ma) Nantuo glacial diamictite as well as in the cap dolostones and shale/siltstones in the lower Doushantuo Formation in eastern Guizhou, southern China. Field occurrences, petrography, and stable sulfur isotopic compositions of pyrite nodules were studied from a section at Taoying, eastern Guizhou, China. Pyrite δ34S values from different nodules varied from 7.3 to 60.5‰ at different stratigraphic levels. No stratigraphic trend existed for the δ34S, supporting the scenario of pyrite formation in sediments before the precipitation of the cap dolostone. Pyrite δ34S values were also homogeneous within individual nodules at a 0.3 to 1 cm sampling scale, but were more heterogeneous at a 2 mm sampling scale. Homogeneity was not expected from the particular model for pyrite nodule formation in a largely closed or semi-closed environment. Thus, differential cementation and compaction of the pyrite-bearing sediments may have produced the nodular shape of the pyrite deposit.